MicroRNA-21 Regulates Diametrically Opposed Biological Functions of Regulatory T Cells - Sun, Jijun; Liu, Ruiling; He, Xiaozhen; Bian, Jiang; Zhao, Wenbo; Shi, Weiyun; Ruan, Qingguo (Frontiers in Immunology, 2021)
Regulatory T cells (Tregs) are considered important for controlling the onset and development of autoimmune disease. Although studies have shown that miR-21 is expressed at higher levels in Treg cells, it remains largely elusive whether miR-21 regulates the immune-suppressive function of Tregs. In the current study, we generated mice lacking miR-21 specifically in their Tregs and investigated the role of miR-21 in regulating Treg function both in vitro and in vivo. Our study revealed that Tregs lacking miR-21 exhibit normal phenotype and unaltered function in suppressing T cell proliferation and dendritic cell activation in vitro. However, compared with miR-21-sufficient Tregs, they produce significant more IL-17 and IL-10 when under pathogenic Th17-priming condition. Adenoviral delivery of miR-21 into Treg cells is able to reduce the expression of both IL-17 and IL-10. Mechanistic study revealed that miR-21 down-regulates IL-10 expression through direct targeting of IL-10, and suppresses reprogramming of Tregs into IL-17-secreting cells through down-regulating Stat3 activity. However, we detected no significant or marginal difference in the development of various autoimmune diseases between wild type mice and mice with Treg-specific deletion of miR-21. In conclusion, our study demonstrated that miR-21 in Tregs regulates diametrically opposed biological Treg functions and is largely dispensable for the development of autoimmune disease.